Murder at the serpentine bridge ebook - Penrose, Andrea (Wrexford & Sloane Mystery, 2022)
For fans of Bridgerton looking for a mysterious twist on the glittering ballrooms of the Regency—a masterfully plotted story from a USA Today bestselling author that combines engaging protagonists with rich historical detail and international intrigue, plus a touch of romance that readers of Amanda Quick and Deanna Raybourn will savor. "[Penrose] mixes well thought out mysteries, early forensic science, great details of the era and a slow burning attraction creating a compulsive read." —The New York Public Library Charlotte, now the Countess of Wrexford, would like nothing more than a summer of peace and quiet with her new husband and their unconventional family and friends. Still, some social obligations must be honored, especially with the grand Peace Celebrations unfolding throughout London to honor victory over Napoleon. But when Wrexford and their two young wards, Raven and Hawk, discover a body floating in Hyde Park's famous lake, that newfound peace looks to be at risk. The late Jeremiah Willis was the engineering genius behind a new design for a top-secret weapon, and the prototype is missing from the Royal Armory's laboratory. Wrexford is tasked with retrieving it before it falls into the wrong hands. But there are unsettling complications to the case—including a family connection. Soon, old secrets are tangling with new betrayals, and as Charlotte and Wrexford spin through a web of international intrigue and sumptuous parties, they must race against time to save their loved ones from harm—and keep the weapon from igniting a new war . . . "A charming, action-packed mix of historical mystery and Regency romance." — Kirkus Reviews "Fascinating and well-researched historic events... a colorful depiction of Regency England." – Publishers Weekly